LABOR MARKET AND EMPLOYMENT IN THE REPUBLIC OF UZBEKISTAN - Radjabova Gavkhar Umarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the actual problem of the modern economy - the problem of employment and the improvement of the labor market. And also, programs aimed at increasing the level of employment of the population.